Morphological description and DNA-based association of the last instar larva of Erotesis schachti Malicky 1982 (Trichoptera: Leptoceridae), an endemic of the Iberian Peninsula - Ruiz-García, Antonio; Lara-Rodríguez, Andrés; Garzón, Andrés; Zamora-Muñoz, Carmen (Zootaxa, 2022)
In this paper we describe the main morphological characteristics that distinguish the full-grown larva of Erotesis schachti, an endemic of the Iberian Peninsula. The conspecificity of the larva and adult was confirmed by DNA analysis. Morphological features that easily discriminate it from the similar species Erotesis baltica are given.